Pendidikan Islam dalam Mengahadapi Era Globalisasi - Humaedi (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2019)
This paper explains about Islamic education in the face of globalization. Islamic education is the effort made by adults towards students in delivering mature levels of thought. The purpose of Islamic education is to direct humans to achieve world and hereafter happiness, Islamic education in the current era of globalization is faced with various problems that must be faced by Islamic education institutions, such problems include public distrust of Islamic educational institutions, lacking a clear vision and mission, curricula that exceed capacity, output of non-competitive educational institutions, inadequate facilities and infrastructure and underdeveloped technology, less professional teaching staff and expertise, the occurrence of the dichotomy of science. In overcoming the problems of Islamic educational institutions, it is necessary to: build public trust in Islamic educational institutions, determine the directed vision and mission in accordance with the Koran and Hadith, improve the performance of educators and education staff, plan curriculum that can answer the challenges of the times, realize empowered graduates high competitiveness, a combination of general science and religion as a form of progressive and modern thought.